Realisasi Fungsi Kelu arga Dalam Pendidikan Anak Menurut Mahasiswa IAIN Salatiga Tahun 2016 - Bahroni Bahroni (State Institute of Islamic Studies (IAIN) Salatiga, 2017)
This study aims to describe in general the realization of family functions, and the realization of family functions in perspective Q.S. Luqman: 13 s.d. 19 in children’s education. The data were collected using questionnaires and interviews to a number of IAIN Salatiga students, and library techniques, data retrieval techniques from various written sources in the context of child education that support data analysis. The results of this study showed that realization of family function in general and in perspective Q.S. Luqman: 13 s.d. 19 in childhood education has been going pretty well, as far as the internal affairs of the student families who are responding in this study. But, when it comes to surrounding communities outside the student family, not all families are fully functioning properly.